Plasma cell type Castleman's disease of lacrimal gland: a case report and literature review - Liangyuan Xu; Jing Li; Xiaolin Xu; Tingting Ren; Jianmin Ma (BMC Ophthalmology, 2024)
Abstract Background Orbital Castleman's disease is a rare benign lymphoproliferative disorder of extranodal origin. Case presentation A 72-year-old man presented with bilateral upper eyelid swelling. Radiology revealed enlarged lacrimal glands in both eyes. Castleman's disease (plasma cell type) was confirmed by histo-immunochemical examinations after excision of the left orbital mass. No extraorbital involvement was found in systemic evaluation. Postoperatively, corticosteroid therapy was given. After 1 year of follow-up, there was no recurrence in the left orbit, and the swelling of the right eyelid was improved. Conclusions Here, we report a case of orbital Castleman's disease involving the lacrimal gland bilaterally and summarize previously reported cases. For bilateral orbital masses, the possibility of Castleman's disease should be considered. Before the diagnosis, it is necessary to fully distinguish from other diseases such as IgG4-related eye diseases.